2019
DOI: 10.33571/rpolitec.v15n30a8
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos nutricionales de peces ornamentales de agua dulce

Abstract: La comercialización de peces ornamentales se ha convertido en una actividad económica de gran importancia para la acuicultura a nivel mundial, destacando la participación de Singapur, España, Japón, Malasia e Indonesia en la lista de principales productores a nivel mundial. Este documento busca recopilar y destacar la importancia de algunos estudios que describen los requerimientos nutricionales en especies ornamentales con potencial productivo y sobresale una problemática local, en donde se toman dietas formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
2
0
2
Order By: Relevance
“…Despite the fact that in this experiment a trend of greater biomass was observed in the juveniles of the 12% lipid treatment, when performing the statistical analysis of the evaluated variables there were no significant differences in: weight, length, total weight gain, weight gained, weight gained per day and specific growth rate (Table 2). This suggests that A. mexicanum has an adaptability to lipid intake, coinciding with Garzón et al (2019) where it was reported for other ornamental fish species such as: Poecilia latipinna, Trichogaster trichoptrus and Pterophyllum scalare that the nutritional requirements necessary for their best performance are in a range of 40 to 50% protein and 6 to 8% lipids. In other cold-water fish such as salmon, it was estimated that a high lipid intake between 15 and 20% contributes to a 13% decrease in the amount of protein in diets, from 48% to 35% without altering their growth, obtaining the same protein efficiency and better energy utilization, attributing this to its energy density (Akoh, 2017).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Despite the fact that in this experiment a trend of greater biomass was observed in the juveniles of the 12% lipid treatment, when performing the statistical analysis of the evaluated variables there were no significant differences in: weight, length, total weight gain, weight gained, weight gained per day and specific growth rate (Table 2). This suggests that A. mexicanum has an adaptability to lipid intake, coinciding with Garzón et al (2019) where it was reported for other ornamental fish species such as: Poecilia latipinna, Trichogaster trichoptrus and Pterophyllum scalare that the nutritional requirements necessary for their best performance are in a range of 40 to 50% protein and 6 to 8% lipids. In other cold-water fish such as salmon, it was estimated that a high lipid intake between 15 and 20% contributes to a 13% decrease in the amount of protein in diets, from 48% to 35% without altering their growth, obtaining the same protein efficiency and better energy utilization, attributing this to its energy density (Akoh, 2017).…”
Section: Resultssupporting
confidence: 83%
“…Today aquaculture is the fastest growing activity worldwide in terms of the production of aquatic organisms (Garzón et al, 2019) and within this activity is the aquarium hobby Citation: Manjarrez-Alcívar, I., Martínez-Cárdenas, L., Vega-Villasante, F., Badillo-Zapata, D., Montoya-Martínez, C. E., & López-Félix, E.F. (2024). Levels of fat for potential consumption of juvenile Ambystoma mexicanum (Shaw & Nodder, 1798) that is based on the hobby of keeping in ornamental aquariums or ponds whether they are fish, crustaceans, mollusks, echinoderms, amphibians and reptiles (Wabnitz et al, 2003;Lango-Reynoso et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De ahí que se hayan agrupado MS, L y C en un mismo cuadrante y los elementos no nitrogenados no tengan relación con los principales indicadores de calidad. Es conocido que la oxidación de la fracción lipídica del músculo en peces es la mayor causa de deterioro, debido al alto grado de insaturación de los L y alta concentración de metales [6,34]. La oxidación de los L posee , 1949).…”
Section: Resultados Y Discusiónunclassified
“…Los aspectos relacionados con la nutrición y alimentación para PO han recibido muy poca atención y aún se desconocen las exigencias nutricionales en muchas especies (Sales & Janssens, 2003); el manejo nutritivo y alimentario carece de rigor técnico, pues responde a la tradición y a eventualidades. En acopios cortos no se acostumbra a suministrar alimentos especializados a los PO; a partir de ocho o diez días los peces reciben principalmente alimentos balanceados de especies de peces de consumo como la tilapia y la trucha (Ortega-Lara et al, 2015), debido a la falta de alimentos balanceados comerciales nacionales y específicos para PO y al costo elevado de los importados, lo que causa una extrapolación de requerimientos nutricionales entre especies (Velasco & Gutiérrez, 2019) .…”
Section: Mercado De Peces Ornamentales En Colombiaunclassified